THE BEAUTIFUL SHARING OF THE THAILAND SHORT FILM “Touching Thai Ad Shows How A Single Act Of Kindness” - Muhammad Iqbal Muttaqin; Muhamad Raihan Adrian; Rayhan Achdika; Adam Muhammad Zidane; Dadan Nurmansyah (Cinematology: Journal Anthology of Film and Television Studies, 2021)
This research focuses on how to promote a product, brand or service to the public. The purpose of this research is how to encourage interest in a product. And the product is a message of humanity, not in the form of goods. The method used, descriptive qualitative is a research method based on the philosophy of postpositivism used to examine the condition of natural objects, where the researcher is the key instrument of data collection techniques carried out by trigulation, data analysis is inductive/qualitative, and the results of qualitative research emphasize meaning. rather than generalization. The results of the study show that the advertising message shown in the film scene contains the principle of sharing/giving alms universally. This film is a representation of a moral message with story elements that exist in the general public. This film is able to understand the message to be conveyed just by looking at the signs without the need to understand the meaning of the language spoken.